Enhanced Methods for Synthesizing Hydroxyxanthone Using Eaton and ZnCl2 Catalyst with Microwave Irradiation - Yuanita, Emmy; Eryani, Farica; Septiyana, Maulida; Lestarini, Ima Arum; Dharmayani, Ni Komang Tri; Sugara, Taufan Hari (Science and Technology Indonesia, 2025)
The methods for synthesizing hydroxyxanthone compounds are continually advancing. Among these, microwave-assisted organic synthesis (MAOS) has emerged as a particularly advantageous technique due to its reduced reaction times, improved yields, and enhanced selectivity. This study reports the efficient synthesis of 3,7 dihydroxyxanthone through the reaction of 2,5-dihydroxybenzoate and resorcinol, using Eaton’s reagent and zinc chloride (ZnCl2) as catalyst under MAOS conditions. The structures of the resulting compounds were analyzed using Fourier-transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (1H-NMR). The efficiency of the catalytic systems was evaluated based on the product yields. The Eaton reagent catalysis resulted in a 9.38% yield of a red solid, while the ZnCl2-catalyzed reaction produced a significantly higher yield of 23.07%, with the product appearing as an orange solid. These results demonstrate that Zn